The Effectiveness of Virtual Reality Exposure Therapy Module for Reducing Acrophobia Symptoms - Fitryanda Akpewila; Muhana Sofiati Utami; Neila Ramdhani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2022)
The amount of places that require a person to be in high-altitude circumstances is a barrier for people who are afraid of heights or also known as acrophobia. The therapist can offer a 3D stimulus using Virtual Reality (VR), making it a more efficient alternative to exposure treatments. Virtual Reality Exposure Therapy is the practice of exposing oneself to a fearful stimulus via a VR camera (VRET). The purpose of this study is to determine the effectiveness of the VRET module in reducing acrophobia symptoms. The pretest-posttest control group design was utilized in the study. Participants with acrophobia were separated into two groups: the control (n=14) and the experimental (n=15) who received VRET treatment. They completed the Acrophobia Questionnaire (AQ) before and after the nine VRET sessions. Compared to control condition, participants in the experimental group reported lower scores in AQ-Anxiety and AQ-Avoidance. Furthermore, each exposure session results in a significant decrease in psychological assessments utilizing the State-Trait Anxiety Inventory and Autonomic Perception Questionnaire scales. A significant decrease has also occurred in the Respiratory Rate and Skin Conductance indicators. According to the findings of this study, the VRET module is effective in reducing the psychological and physiological symptoms of acrophobia.